2014
DOI: 10.1371/journal.pone.0085620
|View full text |Cite
|
Sign up to set email alerts
|

Levofloxacin-Based First-Line Therapy versus Standard First-Line Therapy for Helicobacter pylori Eradication: Meta-Analysis of Randomized Controlled Trials

Abstract: BackgroundFirst-line levofloxacin-based treatments eradicate Helicobacter pylori with varying success. We examined the efficacy and safety of first-line levofloxacin-based treatment in comparison to standard first-line therapy for H pylori eradication.Materials and MethodsWe searched literature databases from Medline, EMBASE, and the Cochrane Register of Randomized Controlled Trials through March 2013 for randomized controlled trials comparing first-line levofloxacin and standard therapy. We included randomize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 39 publications
1
24
0
Order By: Relevance
“…Although not formally compared, the pooled eradication rate of levofl oxacin triple therapy was also higher than clarithromycin triple therapy for 10-14 days (81%, 95% CI, 78-84%). Tolerability of levofl oxacin triple therapy appears to be similar to clarithromycin triple therapy ( 103,138 ).…”
Section: Sequential Therapymentioning
confidence: 99%
“…Although not formally compared, the pooled eradication rate of levofl oxacin triple therapy was also higher than clarithromycin triple therapy for 10-14 days (81%, 95% CI, 78-84%). Tolerability of levofl oxacin triple therapy appears to be similar to clarithromycin triple therapy ( 103,138 ).…”
Section: Sequential Therapymentioning
confidence: 99%
“…However, other studies reported that levofloxacin-containing regimens did not have superior eradication rates compared to other treatments. Metaanalyses and a recent study in 2014 have shown that the outcome of levofloxacin-based first-line therapy was similar to STT [115,116] with an overall crude eradication rate of 79.1% in the levofloxacin group compared to 81.4% in the STT group [116] . A recent RCT in Taiwan with over 153 patients determined there was an advantage to levofloxacin-amoxicillin/clavulanate-PPI therapy over STT, although there was a low eradication rate (ITT analysis: 78.1% vs 57.5%) [117] .…”
Section: Quinolones To Existing Treatmentmentioning
confidence: 89%
“…Recently, however, it has been known that quinolone, that inhibits deoxyribonucleic acid gyrase, is effective in the treatment of H. pylori infection [46][47][48]. Additionally, many studies support that quinolonebased sequential therapy is effective in an area with >15% prevalence of clarithromycin resistant H. pylori strains [49,50].…”
Section: Quinolone-based Sequential Therapymentioning
confidence: 99%